2020
DOI: 10.1051/medsci/2020163
|View full text |Cite
|
Sign up to set email alerts
|

Rétinopathie du prématuré : de la prévention au traitement

Abstract: La rétinopathie du prématuré (ROP) est la principale cause évitable de cécité infantile. Son incidence augmente avec la survie de nouveau-nés extrêmement prématurés. La ROP est une pathologie multi-factorielle du développement de la rétine et du réseau vasculaire rétinien, impliquant des facteurs oxygéno-dépendants et nutritionnels. La multiplicité des facteurs participant à la survenue de la ROP plaide en faveur de stratégies préventives complémentaires et synergiques, telles que le contrôle rigoureux de l’ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…So far, only the relationship between disease development and an increase in VEGF derived from retinal cells secreted in response to neuronal hypoxia has been demonstrated. 45 Several scientific studies have shown that VEGF levels are higher in premature babies than in full-term babies. T. Kaukola showed high VEGF values in studies on the development of the nervous system of premature babies with cardiovascular disorders and placental insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…So far, only the relationship between disease development and an increase in VEGF derived from retinal cells secreted in response to neuronal hypoxia has been demonstrated. 45 Several scientific studies have shown that VEGF levels are higher in premature babies than in full-term babies. T. Kaukola showed high VEGF values in studies on the development of the nervous system of premature babies with cardiovascular disorders and placental insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…First described in 1942 by T. L. Terry as retrolental fibroplasia [ 80 ], retinopathy of prematurity (ROP) is a multi-factorial pathology of retinal development and typically occurs in premature babies, involving the retinal vascular network [ 81 ].…”
Section: Major Retinal Diseases and Oxidative/nitrosative Stressmentioning
confidence: 99%
“…However, it should be noted that the condition can be severe in some cases, leading to blindness if not properly managed. Furthermore, these children reported some complications, including near-sightedness, lazy eyes, crossed eyes, glaucomas, cataracts, and retinal detachment (32)(33)(34). Furthermore, the prognosis in cases with serious central retinopathy is usually favourable since it has been evidenced that most cases return to normal within 3-4 months.…”
Section: Outcomes and Prognosismentioning
confidence: 99%